PENGARUH PROFITABILITAS DAN LIKUIDITAS TERHADAP NILAI PERUSAHAAN DENGANKEBIJAKAN DEVIDEN SEBAGAI PEMODERASI - Fortuna, Cindy; Hastuti, Rini (Jurnal Paradigma Akuntansi, 2023)
Firm value is one of the financial indicators that shows a higher firm value means a higher prosperity of its shareholders. This study aims to determine the effect of profitability and liquidity on firm value with dividend policy as the moderating variable in manufacturing companies listed on the Indonesia Stock Exchange in 2018-2020. The sampling method used in this study is the purposive sampling method and 40 companies were obtained as the valid sample. Multiple regression analysis is used to process the data assisted by Microsoft Excel and Eviews 12. The outcome of this study shows that profitability and liquidity have a negative and insignificant effect on firm value and dividend policy is able to moderate the effect of profitability and liquidity on firm value.